Adjustment Disorders and Quality of Life in Patients With Tracheostomy and Tracheal Cannula: A Scoping Review - Andrea Calderone; Francesco Corallo; Davide Cardile; Carmela Rifici; Fabrizia Caminiti; Valeria Conti‐Nibali; Serena Filoni; Rocco Salvatore Calabrò (Brain and Behavior, 2025)
ABSTRACT Introduction Tracheostomy (TCT) surgery and subsequent tracheal cannula (TC) insertion involve several physical, communicative, and psychological changes for the patient. Decreased mood and dysfunctional states such as morbid anxiety, depression, and stress are often experienced in these clinical situations, and affect the quality of life (QoL) and the rehabilitation process. This review aims to examine the studies in the literature on adjustment disorders (AjD) in patients with TCT or TC and how this affects their QoL during the rehabilitation process. Methods Studies were identified from an online search of PubMed, Cochrane Library, and Embase databases. Studies published between 2013–2023 were selected. This review has been registered on OSF (n): DOI 10.17605/OSF.IO/RHX3J. Results TCT patients were found to experience AjD in terms of anxiety, depression, and stress, which may have a significant impact on QoL and the recovery/extubation time during long‐term rehabilitation. Conclusions The AjD must be considered seriously and carefully during the rehabilitation process in tracheostomized patients, as it can have significant repercussions on the QoL and caregivers. The rehabilitation path must consider the problems linked to this condition: physical, communicative, and psychological.